THE INFLUENCE OF TRUST, MILITARY LEADERSHIP, AND ORGANIZATIONAL ENVIRONMENT ON ORGANIZATIONAL CITIZENSHIP BEHAVIOR WITH ORGANIZATIONAL COMMITMENT AS A MEDIATOR AMONG FIRST OFFICERS IN KOARMADA-I - Muhadi Muhadi; Corry Yohana; Budi Santoso (Green Publisher, 2023)
This study aims to analyze the factors that influence the organizational citizenship behavior of First Officers in Koarmada-I. In this study, the variables selected to be the factors that influence organizational citizenship behavior are trust, leadership, environment and organizational commitment. This research is a type of quantitative research. The sample consisted of 143 respondents who were First Officers in Jakarta's Koarmada-I. The analytical method of this study uses descriptive analysis, validity test, reliability test, and Structural Equation Modeling (SEM) hypothesis testing. The results of the study prove that Trust has a significant effect on Organizational Commitment, Trust has no significant effect on Organizational Citizenship Behavior, Military leadership has no significant effect on Organizational Commitment, Military leadership has a significant effect on Organizational Citizenship Behavior, Environment has a significant effect on Organizational Commitment, Environment has no significant effect on Organizational Citizenship Behavior, Organizational Commitment influences Organizational Citizenship Behavior, There is an indirect effect of Trust on Organizational Citizenship Behavior through Organizational Commitment, There is no indirect effect of Military leadership on Organizational Citizenship Behavior through Organizational Commitment, There is an indirect effect of Environment on Organizational Citizenship Behavior through Organizational Commitment